A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

A mutation within the SH2 domain of slp-76 regulates the tissue distribution and cytokine production of iNKT cells in mice - Danzer, Claudia Agnes; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al. (European Journal of Immunology, 2016)
TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp-76 on iNKT-cell biology. Compared to B6 controls, slp-76(ace/ace) mice carrying a missense mutation (Thr428Ile) within the SH2-domain of slp-76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP-deficient mice. Like ADAP(-/-) iNKT cells, slp-76(ace/ace) iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate-early gene Nur77 and a decreased adhesion to ICAM-1. Furthermore, CD11b-intrinsic effects inhibited cytokine release, concanavalin A-mediated inflammation, and iNKT-cell accumulation in the liver. Unlike B6 and ADAP(-/-) mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP-1-expression was enhanced in slp-76(ace/ace) mice. Blockade of NP-1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP-1 as an iNKT-cell-specific adhesion factor. Thus, slp-76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP-dependent and -independent mechanisms.
EVALuna2:2050

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities. - Günther, Claudia; Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blauth, Michael; Clavel, Thomas; Glaesner, Joachim; Gopalakrishnan, Shreya; Grassl, Guntram A.; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
Keywords: 16S rRNA gene; C57BL/6J; Gut microbiota; Mouse husbandry

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities - Günther, Claudia; Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blaut, Michael; Clavel, Thomas; Gläsner, Joachim; Gopalakrishnan, Shreya; Grassl, Guntram A.; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
Keywords: 16S rRNA gene; C57BL/6J; Gut microbiota; Mouse husbandry

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities - Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blaut, Michael; Clavel, Thomas; Glaesner, Joachim; Gopalakrishnan, Shreya; Grass, Guntram A.; Günther, Claudia; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
EVALuna2:2061

Arginase 1 functions as anti-resolvin in inflammatory bowel disease - Nuese, B.; Gänsbauer, Maximilian; Baier, J.; Mattner, Jochen; Gerlach, Roman; Wirtz, Stefan; Rauh, Manfred (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Bile acids and microbiota: Multifaceted and versatile regulators of the liver–gut axis - Grüner, Niklas; Mattner, Jochen (International Journal of Molecular Sciences, 2021)
After their synthesis from cholesterol in hepatic tissues, bile acids (BAs) are secreted into the intestinal lumen. Most BAs are subsequently re-absorbed in the terminal ileum and are trans-ported back for recycling to the liver. Some of them, however, reach the colon and change their physicochemical properties upon modification by gut bacteria, and vice versa, BAs also shape the composition and function of the intestinal microbiota. This mutual interplay of both BAs and gut microbiota regulates many physiological processes, including the lipid, carbohydrate and energy metabolism of the host. Emerging evidence also implies an important role of this enterohepatic BA circuit in shaping mucosal colonization resistance as well as local and distant immune responses, tissue physiology and carcinogenesis. Subsequently, disrupted interactions of gut bacteria and BAs are associated with many disorders as diverse as Clostridioides difficile or Salmonella Typhimurium infection, inflammatory bowel disease, type 1 diabetes, asthma, metabolic syndrome, obesity, Par-kinson’s disease, schizophrenia and epilepsy. As we cannot address all of these interesting under-lying pathophysiologic mechanisms here, we summarize the current knowledge about the physio-logic and pathogenic interplay of local site microbiota and the enterohepatic BA metabolism using a few selected examples of liver and gut diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Bile acids; Enterohepatic recirculation; Host–microbe interactions; Intestinal microbiota; Microbial metabolism

CD101 as an indicator molecule for pathological changes at the interface of host-microbiota interactions - Wrage, Marius; Kaltwasser, Johanna; Menge, Sonja; Mattner, Jochen (International Journal of Medical Microbiology, 2021)
Intestinal microbiota signal to local and distant tissues in the body. Thus, they also regulate biochemical, metabolic and immunological processes in the gut and in the pancreas. Vice versa, eating habits or the immune system of the host shape the intraluminal microbiota. Disruptions of these versatile host-microbiota interactions underlie the pathogenesis of complex immune-mediated disorders such as inflammatory bowel disease (IBD) or type 1 diabetes (T1D). Consequently, dysbiosis and increased intestinal permeability associated with both disorders change the biology of underlying tissues, as evidenced, for example, by an altered expression of surface markers such as CD101 on immune cells located at these dynamic host-microbiota interfaces. CD101, a heavily glycosylated member of the immunoglobulin superfamiliy, is predominantly detected on myeloid cells, intraepithelial lymphocytes (IELs) and regulatory T cells (Tregs) in the gut. The expression of CD101 on both myeloid cells and T lymphocytes protects from experimental enterocolitis and T1D. The improved outcome of both diseases is associated with an anti-inflammatory cytokine profile and a reduced expansion of T cells. However, distinct bacteria suppress the expression of CD101 on myeloid cells, similar as does inflammation on T cells. Thus, the reduced CD101 expression in T1D and IBD patients might be a consequence of an altered composition of the intestinal microbiota, enhanced bacterial translocation and a subsequent primining of local and systemic inflammatory immune responses.
CRIS-Team Scopus Importer:2021-04-09
Keywords: CD101; Host-microbe interactions; Immune-mediated disease; Microbiota; Mucosal surfaces

CD101 inhibits the expansion of colitogenic T cells - Schey, Regina; Dornhoff, H.; Baier, J. L. C.; Purtak, M.; Opoka, R.; Koller, A. K.; Atreya, Raja; Rau, Tilman; Daniel, Christoph; Amann, Kerstin Ute; Bogdan, Christian; Mattner, Jochen (Mucosal Immunology, 2016)
CD101 exerts negative-costimulatory effects in vitro, but its function in vivo remains poorly defined. CD101 is abundantly expressed on lymphoid and myeloid cells in intestinal tissues, but absent from naïve splenic T cells. Here, we assessed the impact of CD101 on the course of inflammatory bowel disease (IBD). Using a T-cell transfer model of chronic colitis, we found that in recipients of naïve T cells from CD101(+/+) donors up to 30% of the recovered lymphocytes expressed CD101, correlating with an increased interleukin (IL)-2-mediated FoxP3 expression. Transfer of CD101(-/-) T cells caused more severe colitis and was associated with an expansion of IL-17-producing T cells and an enhanced expression of IL-2R?/? independently of FoxP3. The co-transfer of naïve and regulatory T cells (Treg) protected most effectively from colitis, when both donor and recipient mice expressed CD101. Although the expression of CD101 on T cells was sufficient for Treg-function and the inhibition of T-cell proliferation, sustained IL-10 production required additional CD101 expression by myeloid cells. Finally, in patients with IBD a reduced CD101 expression on peripheral and intestinal monocytes and CD4(+) T cells correlated with enhanced IL-17 production and disease activity. Thus, CD101 deficiency is a novel marker for progressive colitis and potential target for therapeutic intervention.
EVALuna2:2051

Cd101 is a type 1 diabetes susceptibility gene in NOD mice - Mattner, Jochen; Wicker, L. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

CD83 orchestrates immunity toward self and non-self in dendritic cells - Wild, Andreas; Krzyzak, Lena; Peckert, Katrin; Stich, Lena; Kuhnt, Christine; Butterhof, Alina; Seitz, Christine; Mattner, Jochen; Grner, Niklas; Gänsbauer, Maximilian; Purtak, Martin; Soulat, Didier; et al. (JCI Insight, 2019)
Dendritic cells (DCs) are crucial to balance protective immunity and autoimmune inflammatory processes. Expression of CD83 is a well-established marker for mature DCs, although its physiological role is still not completely understood. Using a DC-specific CD83-conditional KO (CD83(Delta DC)) mouse, we provide new insights into the function of CD83 within this cell type. Interestingly, CD83-deficient DCs produced drastically increased IL-2 levels and displayed higher expression of the costimulatory molecules CD25 and OX40L, which causes superior induction of antigen-specific T cell responses and compromises Treg suppressive functions. This also directly translates into accelerated immune responses in vivo. Upon Salmonella typhimurium and Listeria monocytogenes infection, CD83(Delta DC) mice cleared both pathogens more efficiently, and CD83-deficient DCs expressed increased IL-12 levels after bacterial encounter. Using the experimental autoimmune encephalomyelitis model, autoimmune inflammation was dramatically aggravated in CD83(Delta DC) mice while resolution of inflammation was strongly reduced. This phenotype was associated with increased cell influx into the CNS accompanied by elevated Th17 cell numbers. Concomitantly, CD83(Delta DC) mice had reduced Treg numbers in peripheral lymphoid organs. In summary, we show that CD83 ablation on DCs results in enhanced immune responses by dysregulating tolerance mechanisms and thereby impairing resolution of inflammation, which also demonstrates high clinical relevance.
CRIS-Team WoS Importer:2019-11-01

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Compartmentalized immune responses and the local microbiota determine mucosal and systemic immunity against SARS-CoV-2 - Buttenschön, Jonas; Vogt, Stefan; Mattner, Jochen (Cellular & Molecular Immunology, 2022)
CRIS-Team WoS Importer:2022-01-14

Dendritic Cells Control Regulatory T Cell Function Required for Maintenance of Intestinal Tissue Homeostasis - Hilpert, Cornelia; Sitte, Selina; Arnold, Harald; Lehmann, Christian; Dudziak, Diana; Mattner, Jochen; Vöhringer, David (Journal of Immunology, 2019)
Dendritic cells (DCs) together with regulatory T cells (Tregs) are essential mediators of immune homeostasis. Disruption of function or frequency of either cell type can lead to fatal autoimmunity. We previously described that mice constitutively lacking DCs (∆DC) develop autoimmunity characterized by reduced body weight, autoantibodies, and pronounced intestinal inflammation. In this study, we show that lack of DCs leads to an altered gene expression profile in peripheral but not thymic Tregs with increased expression of inhibitory receptors. The suppressive function of Tregs from ΔDC mice was impaired in T cell cocultures. In a model of transfer colitis, Tregs from ∆DC mice were only functional in the presence of DCs in recipient mice. Lack of MHC class II on DCs also resulted in upregulation of inhibitory receptors on Tregs, reduced body weight, and elevated serum IgA levels. Further analysis of the IgA response revealed an expansion of IgA+ germinal center B cells and plasma cells in mesenteric lymph nodes and more IgA-coated commensal bacteria in feces of ∆DC mice. Thus, we show a critical role for DCs to establish intestinal homeostasis by regulating Treg function for prevention of spontaneous inflammation.
CRIS-Team Scopus Importer:2019-11-29

Faecal microbiota transplantation-A clinical view - Mattner, Jochen; Schmidt, F.; Siegmund, B. (International Journal of Medical Microbiology, 2016)
Faecal microbiota transplantation has gained increasing attention over the last decade as various phenotypes could be transferred from a donor to a recipient in different animal models. Clinically, however, the sole indication with evidence from a randomized placebo controlled trial is refractory Clostridium difficile infection. Despite revealing successful clinical outcomes, questions concerning regulatory affairs, the identification of the best donor, the optimal mixture of the transplant as well as the preferred route of administration remain to be clarified even for this indication. Initiated by the idea that alterations in the composition of the intestinal microbiota are associated with intestinal inflammation in inflammatory bowel disease, several studies investigated whether faecal microbiota transplantation would be an equally suitable approach for these devastating disorders. Indeed, the available data indicate changes in the microbiota composition following faecal microbial transplantation depending on the degree of intestinal inflammation. Furthermore, first data even provide evidence that the transplantation of an "optimized" microbiota induces clinical remission in ulcerative colitis. However, despite these intriguing results it needs to be considered that not only "a cure of inflammation", but also risk factors and phenotypes including obesity can be transferred via faecal microbiota transplantation. Thus, a deeper understanding of the impact of a distinct microbiota composition is required before "designing" the optimal faecal microbiota transplant.
EVALuna2:7702

Friend or Foe? The Ambiguous Role of Innate Lymphoid Cells in Cancer Development - Mattner, Jochen; Wirtz, Stefan (Trends in Immunology, 2017)
The development of immunotherapies represents a major advance towards the effective eradication of malignant tumors. So far, therapeutic approaches have largely focused on T lymphocytes, but the innate arm of the immune system might be similarly important. Innate lymphoid cells (ILCs) are rapidly-responding cells that are functionally analogous to diverse T cell subsets. In recent years these cells have attracted enormous attention owing to their pleiotropic effects in early host defense to infection and organ pathologies. ILCs might also represent promising targets in the context of cancer therapy because they are an innate immune cell population endowed with potent immunomodulatory properties. In this review we discuss the impact of the three ILC subsets and the signature cytokines they release on cancer development and tumor growth.
EVALuna2:7741

Genetic and functional data identifying Cd101 as a type 1 diabetes (T1D) susceptibility gene in nonobese diabetic (NOD) mice - Mattner, Jochen; Mohammed, Javid P.; Fusakio, Michael E.; Giessler, Claudia; Hackstein, Carl Philipp; Opoka, Robert; Wrage, Marius; Schey, Regina; Clark, Jan; Fraser, Heather I.; Rainbow, Daniel B.; Wicker, Linda S. (PLoS Genetics, 2019)
Type 1 diabetes (T1D) is a chronic multi-factorial disorder characterized by the immune-mediated destruction of insulin-producing pancreatic beta cells. Variations at a large number of genes influence susceptibility to spontaneous autoimmune T1D in non-obese diabetic (NOD) mice, one of the most frequently studied animal models for human disease. The genetic analysis of these mice allowed the identification of many insulin-dependent diabetes (Idd) loci and candidate genes, one of them being Cd101. CD101 is a heavily glycosylated transmembrane molecule which exhibits negative-costimulatory functions and promotes regulatory T (Treg) function. It is abundantly expressed on subsets of lymphoid and myeloid cells, particularly within the gastrointestinal tract. We have recently reported that the genotype-dependent expression of CD101 correlates with a decreased susceptibility to T1D in NOD.B6 Idd10 congenic mice compared to parental NOD controls. Here we show that the knockout of CD101 within the introgressed B6-derived Idd10 region increased T1D frequency to that of the NOD strain. This loss of protection from T1D was paralleled by decreased Gr1-expressing myeloid cells and FoxP3+ Tregs and an enhanced accumulation of CD4-positive over CD8-positive T lymphocytes in pancreatic tissues. As compared to CD101+/+ NOD.B6 Idd10 donors, adoptive T cell transfers from CD101-/- NOD.B6 Idd10 mice increased T1D frequency in lymphopenic NOD scid and NOD.B6 Idd10 scid recipients. Increased T1D frequency correlated with a more rapid expansion of the transferred CD101-/- T cells and a lower proportion of recipient Gr1-expressing myeloid cells in the pancreatic lymph nodes. Fewer of the Gr1+ cells in the recipients receiving CD101-/- T cells expressed CD101 and the cells had lower levels of IL-10 and TGF-β mRNA. Thus, our results connect the Cd101 haplotype-dependent protection from T1D to an anti-diabetogenic function of CD101-expressing Tregs and Gr1-positive myeloid cells and confirm the identity of Cd101 as Idd10.
CRIS-Team Scopus Importer:2019-07-09

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

Immune responses to tumor-unrelated antigens might predict adverse effects in patients treated with anti-PD-1 immunotherapy - Nuse, Bjorn; Holland, Tim; Mattner, Jochen (Cellular & Molecular Immunology, 2022)
CRIS-Team WoS Importer:2022-12-02

Impact of Microbes on the Pathogenesis of Primary Biliary Cirrhosis (PBC) and Primary Sclerosing Cholangitis (PSC) - Mattner, Jochen (International Journal of Molecular Sciences, 2016)
Primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC) represent the major clinical entities of chronic cholestatic liver diseases. Both disorders are characterized by portal inflammation and slowly progress to obliterative fibrosis and eventually liver cirrhosis. Although immune-pathogenic mechanisms have been implicated in the pathogenesis of PBC and PSC, neither disorder is considered to be a classical autoimmune disease, as PSC and PBC patients do not respond to immune-suppressants. Furthermore, the decreased bile flow resulting from the immune-mediated tissue assault and the subsequent accumulation of toxic bile products in PBC and PSC not only perpetuates biliary epithelial damage, but also alters the composition of the intestinal and biliary microbiota and its mutual interactions with the host. Consistent with the close association of PSC and inflammatory bowel disease (IBD), the polyclonal hyper IgM response in PBC and (auto-)antibodies which cross-react to microbial antigens in both diseases, an expansion of individual microbes leads to shifts in the composition of the intestinal or biliary microbiota and a subsequent altered integrity of epithelial layers, promoting microbial translocation. These changes have been implicated in the pathogenesis of both devastating disorders. Thus, we will discuss here these recent findings in the context of novel and alternative therapeutic options.
EVALuna:33884

Intestinal eosinophils: characterization of elusive granulocytes as anti-bacterial and immunomodulatory effector cells in colitis - Holland, Tim; Mattner, Jochen (Signal Transduction and Targeted Therapy, 2023)
CRIS-Team Scopus Importer:2023-09-08

Involvement of interleukin-18 in the pathogenesis of human eosinophilic esophagitis - Niranjan, Rituraj; Rajavelu, Priya; Ventateshaiah, Sathisha Upparahalli; Shukla, Jai Shankar; Zaidi, Asifa; Mariswamy, Siddesha Jalahalli; Mattner, Jochen; Fortgang, Liana; Kowalczyk, Monika; Balart, Luis; Shukla, Anshi; Mishra, Anil (Clinical Immunology, 2015)
IL-18 is induced in food allergy and EoE is food allergen-induced disease. Therefore, we tested the hypothesis whether IL-18 is involved in food allergen-induced EoE pathogenesis. Accordingly, we examined normal SPT+ and SPT- EoE patient blood and biopsy samples for IL-18, IL-18R?, ICAM and VCAM expression. Herein, we show increased IL-18 level is highly significant in food allergen SPT+ compared to SPT- EoE patients. We also report that IL-18R?+ cells and mRNA levels are induced in the esophageal biopsies of EoE patients and blood IL-18 levels correlate with esophageal eosinophilia (P<0.01). Additionally, we report that the levels of esophageal eosinophil and mast cells correlate with ICAM expression in human EoE. Mechanistically, we show that IL-18 in vitro stimulates iNKT cells and endothelial cells and induce eosinophil active cytokines IL-5 and IL-13. We provide the evidence that IL-18 is critical cytokine involved in activation of iNKT cells and ICAM in promoting human EoE.
EVALuna2:7684

L-arginine as a novel target for clinical intervention in inflammatory bowel disease - Nüse, Björn; Mattner, Jochen (Exploration of Immunology, 2021)
Arginase-1 (Arg1) and the inducible nitric oxide synthase 2 (NOS2) compete for the common substrate L-arginine, semi-essential amino acid, and central intestinal metabolite. Both enzymes exhibit various, sometimes opposing effects on immune responses, tissue regeneration, or microbial growth and replication. In sub-mucosal tissues of patients suffering from inflammatory bowel disease (IBD), similar as in experimental colitis, the expression and activity of both enzymes, Arg1 and NOS2 are more prominent than in respective controls. Accordingly, the metabolism of L-arginine is altered in IBD patients. Thus, L-arginine represents a promising medical target for clinical intervention in these devastating diseases. Previous studies primarily focused on the host side of L-arginine metabolism. Initial reports using Arg1 inhibitors generated conflicting results in murine colitis models. Subsequently, only the generation of conditional Arg1 knockout mice allowed reliable functional analyses of Arg1 and the L-arginine metabolism in the immune system. Utilizing cell-specific conditional Arg1 knockouts, we have recently reported that Arg1, surprisingly, hampered the resolution of experimental colitis due to the restriction of the intraluminal availability of L-arginine. Reduced levels of L-arginine restrained the compositional diversity of the intestinal microbiota and subsequently the mutual metabolism between the microbiota and the host. Thus, the intraluminal microbiota represents a potential therapeutic target for L-arginine metabolism aside from host-dependent L-arginine consumption.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Arginase-1; colitis; gut microbiota; inflammatory bowel disease; intestinal metabolism; L-arginine

L-arginine metabolism as pivotal interface of mutual host–microbe interactions in the gut - Nüse, Björn; Holland, Tim; Rauh, Manfred; Gerlach, Roman; Mattner, Jochen (Gut Microbes, 2023)
L-arginine (L-arg) is a versatile amino acid and a central intestinal metabolite in mammalian and microbial organisms. Thus, L-arg participates as precursor of multiple metabolic pathways in the regulation of cell division and growth. It also serves as a source of carbon, nitrogen, and energy or as a substrate for protein synthesis. Consequently, L-arg can simultaneously modify mammalian immune functions, intraluminal metabolism, intestinal microbiota, and microbial pathogenesis. While dietary intake, protein turnover or de novo synthesis usually supply L-arg in sufficient amounts, the expression of several key enzymes of L-arg metabolism can change rapidly and dramatically following inflammation, sepsis, or injury. Consequently, the availability of L-arg can be restricted due to increased catabolism, transforming L-arg into an essential amino acid. Here, we review the enzymatic pathways of L-arg metabolism in microbial and mammalian cells and their role in immune function, intraluminal metabolism, colonization resistance, and microbial pathogenesis in the gut.
CRIS-Team Scopus Importer:2023-07-21
Keywords: colonization resistance; dietary L-arg supplementation; host–microbe interaction; intestinal microbiota; L-arginine (L-arg); microbial pathogenesis; mucosal immune function; mutual metabolic pathways; virulence factor

Mechanisms of autoimmune liver disease - Baier, Julia; Mattner, Jochen (Discovery medicine, 2014)
The immune system of the liver is characterized by a predominant innate component. Several innate immune cell populations have been implicated in the pathogenesis of immune-mediated hepatic diseases, which are frequently associated with systemic symptoms or with co-morbidities affecting other organ systems. Thus, next to tissue-specific factors, general tolerance mechanisms are affected in devastating hepatic disorders like primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), or primary biliary cirrhosis (PBC). The innate immune cell populations abundantly detected within the liver and endowed with potent immunomodulatory capacities include innate lymphoid cells (ILCs) and natural killer T (NKT) cells. While both ILCs and NKT cells can be activated by different cytokines and/or chemokines, NKT cells also respond to (glyco-) lipid antigens engaging their canonical, semi-invariant TCR. Once activated, ILCs and NKT cells release copious amounts of Th1, Th2, and/or Th17 cytokines that shape subsequent innate and adaptive immune responses. Those immunomodulatory features as well as the recently described antigen-presenting capacity of ILCs and/or the bi-directional functional role of NKT cells might not only underlie the pathogenic mechanisms in the respective disorders, but also provide promising targets for clinical intervention. We will discuss these novel aspects as well as the role of alarmin-like cytokines such as IL-33 in the context of ILC and NKT cell activation and the consequences for the induction and progress of hepatic tissue damage and fibrosis.
EVALuna2:7662

Mechanisms of Innate Lymphoid Cell and Natural Killer T Cell Activation during Mucosal Inflammation - Nau, David; Altmayer, Nora; Mattner, Jochen (Journal of Immunology Research, 2014)
Mucosal surfaces in the airways and the gastrointestinal tract are critical for the interactions of the host with its environment. Due to their abundance at mucosal tissue sites and their powerful immunomodulatory capacities, the role of innate lymphoid cells (ILCs) and natural killer T (NKT) cells in the maintenance of mucosal tolerance has recently moved into the focus of attention. While NKT cells as well as ILCs utilize distinct transcription factors for their development and lineage diversification, both cell populations can be further divided into three polarized subpopulations reflecting the distinction into Th1, Th2, and Th17 cells in the adaptive immune system. While bystander activation through cytokines mediates the induction of ILC and NKT cell responses, NKT cells become activated also through the engagement of their canonical T cell receptors (TCRs) by (glyco)lipid antigens (cognate recognition) presented by the atypical MHC I like molecule CD1d on antigen presenting cells (APCs). As both innate lymphocyte populations influence inflammatory responses due to the explosive release of copious amounts of different cytokines, they might represent interesting targets for clinical intervention. Thus, we will provide an outlook on pathways that might be interesting to evaluate in this context.
EVALuna2:7650

Metaplastic epithelial cells: origination from stem cells and promotion of intestinal inflammation - Holland, Tim; Mattner, Jochen (Signal Transduction and Targeted Therapy, 2025)
CRIS-Team Scopus Importer:2025-03-21

Natural killer T (NKT) cells in autoimmune hepatitis - Mattner, Jochen (Current Opinion in Immunology, 2013)

NKT Cells Contribute to the Control of Microbial Infections - Vogt, Sabine; Mattner, Jochen (Frontiers in Cellular and Infection Microbiology, 2021)
Innate (-like) T lymphocytes such as natural killer T (NKT) cells play a pivotal role in the recognition of microbial infections and their subsequent elimination. They frequently localize to potential sites of pathogen entry at which they survey extracellular and intracellular tissue spaces for microbial antigens. Engagement of their T cell receptors (TCRs) induces an explosive release of different cytokines and chemokines, which often pre-exist as constitutively expressed gene transcripts in NKT cells and underlie their poised effector state. Thus, NKT cells regulate immune cell migration and activation and subsequently, bridge innate and adaptive immune responses. In contrast to conventional T cells, which react to peptide antigens, NKT cells recognize lipids presented by the MHC class I like CD1d molecule on antigen presenting cells (APCs). Furthermore, each NKT cell TCR can recognize various antigen specificities, whereas a conventional T lymphocyte TCR reacts mostly only to one single antigen. These lipid antigens are either intermediates of the intracellular APC`s-own metabolism or originate from the cell wall of different bacteria, fungi or protozoan parasites. The best-characterized subset, the type 1 NKT cell subset expresses a semi-invariant TCR. In contrast, the TCR repertoire of type 2 NKT cells is diverse. Furthermore, NKT cells express a panoply of inhibitory and activating NK cell receptors (NKRs) that contribute to their primarily TCR-mediated rapid, innate like immune activation and even allow an adaption of their immune response in an adoptive like manner. Dueto their primary localization at host-environment interfaces, NKT cells are one of the first immune cells that interact with signals from different microbial pathogens. Vice versa, the mutual exchange with local commensal microbiota shapes also the biology of NKT cells, predominantly in the gastrointestinal tract. Following infection, two main signals drive the activation of NKT cells: first, cognate activation upon TCR ligation by microbial or endogenous lipid antigens; and second, bystander activation due to cytokines. Here we will discuss the role of NKT cells in the control of different microbial infections comparing pathogens expressing lipid ligands in their cell walls to infectious agents inducing endogenous lipid antigen presentation by APCs.
CRIS-Team WoS Importer:2021-10-22

Novel plasmids in multidrug-resistant Shigella flexneri serotypes from Pakistan - Nisa, Iqbal; Driessen, Arnold; Nijland, Jeroen; Rahman, Hazir; Mattner, Jochen; Qasim, Muhammad (Archives of Microbiology, 2023)
Shigellosis is the main cause of food and waterborne diarrhea and is an emerging threat to human health. The current study characterized the indigenous multidrug-resistant Shigella flexneri serotypes for their plasmid profiles and genetic diversity, to characterize the plasmid evolutionary patterns and distribution. In total, 199 identified S. flexneri isolates belonging to six different serotypes were analyzed for plasmid profiling, followed by an analysis of whole genome sequencing. All isolates of S. flexneri resistant to antibiotics harbored multiple copies of plasmids with sizes ranging from 1.25 kbp to 9.4 kbp. These isolates were clustered into 22 distinct plasmid patterns, labeled as p1-p22. Among these, p1 (24%) and p10 (13%) were the predominant plasmid profiles. All S. flexneri strains were grouped into 12 clades with a 75% similarity level. Also, a significant association was observed among the plasmid patterns, p23 and p17 with the drug-resistant patterns AMC, SXT, C (19.5%) and OFX, AMC, NA, CIP (13.5%), respectively. Moreover, the most widespread plasmid patterns p4, p10, and p1 showed a significant association with the serotypes 1b (29.16%), 2b (36%), and 7a (100%), respectively. After plasmid sequence assembly and annotation analysis, a variety of small plasmids that vary in size from 973 to 6200 bp were discovered. Many of these plasmids displayed high homology and coverage with plasmids from non-S. flexneri. Several novel plasmids of small size were discovered in multidrug-resistant S. flexneri. The data also showed that plasmid profile analysis is more consistent than antibiotic susceptibility pattern analysis for identifying epidemic strains of S. flexneri isolated in Pakistan.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Multidrug-resistant Shigella flexneri; Pakistan; Plasmids; Whole genome sequencing

Otubain 2 promotes muramyl dipeptide-mediated anti-colitogenic effects due to de-ubiquitination of receptor interaction protein 2 - Mattner, Jochen (Clinical and Translational Discovery, 2024)
CRIS-Team Scopus Importer:2024-11-01

Perturbations of mucosal homeostasis through interactions of intestinal microbes with myeloid cells - Schey, Regina; Danzer, Claudia Agnes; Mattner, Jochen (Immunobiology, 2015)
Mucosal surfaces represent the largest areas of interactions of the host with its environment. Subsequently, the mucosal immune system has evolved complex strategies to maintain the integrity of the host by inducing protective immune responses against pathogenic and tolerance against dietary and commensal microbial antigens within the broad range of molecules the intestinal epithelium is exposed to. Among many other specialized cell subsets, myeloid cell populations - due to their strategic location in the subepithelial lamina propria - are the first ones to scavenge and process these intestinal antigens and to send consecutive signals to other immune and non-immune cell subsets. Thus, myeloid cell populations represent attractive targets for clinical intervention in chronic inflammatory bowel diseases (IBDs) such as ulcerative colitis (UC) and Crohn's disease (CD) as they initiate and modulate inflammatory or regulatory immune response and shape the intestinal T cell pool. Here, we discuss the interactions of the intestinal microbiota with dendritic cell and macrophage populations and review in this context the literature on four promising candidate molecules that are critical for the induction and maintenance of intestinal homeostasis on the one hand, but also for the initiation and propagation of chronic intestinal inflammation on the other.
EVALuna2:7664

Pivotal Role of Intestinal Microbiota and Intraluminal Metabolites for the Maintenance of Gut-Bone Physiology - Grüner, Niklas; Ortlepp, Anna Lisa; Mattner, Jochen (International Journal of Molecular Sciences, 2023)
Intestinal microbiota, and their mutual interactions with host tissues, are pivotal for the maintenance of organ physiology. Indeed, intraluminal signals influence adjacent and even distal tissues. Consequently, disruptions in the composition or functions of microbiota and subsequent altered host-microbiota interactions disturb the homeostasis of multiple organ systems, including the bone. Thus, gut microbiota can influence bone mass and physiology, as well as postnatal skeletal evolution. Alterations in nutrient or electrolyte absorption, metabolism, or immune functions, due to the translocation of microbial antigens or metabolites across intestinal barriers, affect bone tissues, as well. Intestinal microbiota can directly and indirectly alter bone density and bone remodeling. Intestinal dysbiosis and a subsequently disturbed gut-bone axis are characteristic for patients with inflammatory bowel disease (IBD) who suffer from various intestinal symptoms and multiple bone-related complications, such as arthritis or osteoporosis. Immune cells affecting the joints are presumably even primed in the gut. Furthermore, intestinal dysbiosis impairs hormone metabolism and electrolyte balance. On the other hand, less is known about the impact of bone metabolism on gut physiology. In this review, we summarized current knowledge of gut microbiota, metabolites and microbiota-primed immune cells in IBD and bone-related complications.
CRIS-Team Scopus Importer:2023-04-07
Keywords: arthritis; cell trafficking; cytokines; gut–bone axis; hormone and electrolyte metabolism; inflammatory bowel disease; intestinal dysbiosis; intestinal microbiota; osteoporosis; spondyloarthropathy

Shigella Outer Membrane Vesicles as Promising Targets for Vaccination - Qasim, Muhammad; Wrage, Marius; Nüse, Björn; Mattner, Jochen (International Journal of Molecular Sciences, 2022)
The clinical symptoms of shigellosis, a gastrointestinal infection caused by Shigella spp. range from watery diarrhea to fulminant dysentery. Endemic infections, particularly among children in developing countries, represent the majority of clinical cases. The situation is aggravated due to the high mortality rate of shigellosis, the rapid dissemination of multi-resistant Shigella strains and the induction of only serotype-specific immunity. Thus, infection prevention due to vaccination, encompassing as many of the circulating serotypes as possible, has become a topic of interest. However, vaccines have turned out to be ineffective so far. Outer membrane vesicles (OMVs) are promising novel targets for vaccination. OMVs are constitutively secreted by Gram-negative bacteria including Shigella during growth. They are composed of soluble luminal portions and an insoluble membrane and can contain toxins, bioactive periplasmic and cytoplasmic (lipo-) proteins, (phospho-) lipids, nucleic acids and/or lipopolysaccharides. Thus, OMVs play an important role in bacterial cell– cell communication, growth, survival and pathogenesis. Furthermore, they modulate the secretion and transport of biomolecules, the stress response, antibiotic resistance and immune responses of the host. Thus, OMVs serve as novel secretion machinery. Here, we discuss the current literature and highlight the properties of OMVs as potent vaccine candidates because of their immunomodulatory, antigenic and adjuvant properties.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Outer membrane vesicles (OMVs); Shigella; Vaccination

Slp-76 is a critical determinant of NK-cell mediated recognition of missing-self targets - Lampe, Kristin; Endale, Mehari; Cashman, Siobhan; Fang, Hao; Mattner, Jochen; Hildeman, David; Hoebe, Kasper (European Journal of Immunology, 2015)
Absence of MHC class I expression is an important mechanism by which NK cells recognize a variety of target cells, yet the pathways underlying "missing-self" recognition, including the involvement of activating receptors, remain poorly understood. Using ethyl-N-nitrosourea mutagenesis in mice, we identified a germline mutant, designated Ace, with a marked defect in NK cell mediated recognition and elimination of "missing-self" targets. The causative mutation was linked to chromosome 11 and identified as a missense mutation (Thr428Ile) in the SH2 domain of Slp-76-a critical adapter molecule downstream of ITAM-containing surface receptors. The Slp-76 Ace mutation behaved as a hypomorphic allele-while no major defects were observed in conventional T-cell development/function, a marked defect in NK cell mediated elimination of ?2-microglobulin (?2M) deficient target cells was observed. Further studies revealed Slp-76 to control NK-cell receptor expression and maturation; however, activation of Slp-76(ace/ace) NK cells through ITAM-containing NK-cell receptors or allogeneic/tumor target cells appeared largely unaffected. Imagestream analysis of the NK-?2M(-/-) target cell synapse revealed a specific defect in actin recruitment to the conjugate synapse in Slp-76(ace/ace) NK cells. Overall these studies establish Slp-76 as a critical determinant of NK-cell development and NK cell mediated elimination of missing-self target cells in mice.
EVALuna2:7683

STAT1 coordinates intestinal epithelial cell death during gastrointestinal infection upstream of Caspase-8 - Stolzer, Iris; Schickedanz, Laura; Chiriac, Mircea T.; López-Posadas, Rocío; Grassl, Guntram A.; Mattner, Jochen; Wirtz, Stefan; Neurath, Markus; Günther, Claudia; Winner, Beate (Mucosal Immunology, 2021)
Intestinal homeostasis and the maintenance of the intestinal epithelial barrier are essential components of host defense during gastrointestinal Salmonella Typhimurium infection. Both require a strict regulation of cell death. However, the molecular pathways regulating epithelial cell death have not been completely understood. Here, we elucidated the contribution of central mechanisms of regulated cell death and upstream regulatory components during gastrointestinal infection. Mice lacking Caspase-8 in the intestinal epithelium are highly sensitive towards bacterial induced enteritis and intestinal inflammation, resulting in an enhanced lethality of these mice. This phenotype was associated with an increased STAT1 activation during Salmonella infection. Cell death, barrier breakdown and systemic infection were abrogated by an additional deletion of STAT1 in Casp8ΔIEC mice. In the absence of epithelial STAT1, loss of epithelial cells was abolished which was accompanied by a reduced Caspase-8 activation. Mechanistically, we demonstrate that epithelial STAT1 acts upstream of Caspase-8-dependent as well as -independent cell death and thus might play a major role at the crossroad of several central cell death pathways in the intestinal epithelium. In summary, we uncovered that transcriptional control of STAT1 is an essential host response mechanism that is required for the maintenance of intestinal barrier function and host survival.
CRIS-Team Scopus Importer:2021-09-17

Synthetic Lipoteichoic Acid Glycans Are Potential Vaccine Candidates to Protect from Clostridium difficile Infections - Broecker, Felix; Martin, Christopher E.; Wegner, Erik; Mattner, Jochen; Baek, Ju Yuel; Pereira, Claney L.; Anish, Chakkumkal; Seeberger, Peter H. (Cell Chemical Biology, 2016)
Infections with Clostridium difficile increasingly cause morbidity and mortality worldwide. Bacterial surface glycans including lipoteichoic acid (LTA) were identified as auspicious vaccine antigens to prevent colonization. Here, we report on the potential of synthetic LTA glycans as vaccine candidates. We identified LTA-specific antibodies in the blood of C. difficile patients. Therefore, we evaluated the immunogenicity of a semi-synthetic LTA-CRM197 glycoconjugate. The conjugate elicited LTA-specific antibodies in mice that recognized natural LTA epitopes on the surface of C. difficile bacteria and inhibited intestinal colonization of C. difficile in mice in vivo. Our findings underscore the promise of synthetic LTA glycans as C. difficile vaccine candidates.
EVALuna2:7716

Synthetic Oligosaccharide-Based Vaccines Protect Mice from Clostridioides difficile Infections - Broecker, Felix; Wegner, Erik; Seco, Bruna M.S.; Kaplonek, Paulina; Bräutigam, Maria; Enßer, Armin; Pfister, Frederick; Daniel, Christoph; Martin, Christopher E.; Mattner, Jochen; Seeberger, Peter H. (ACS Chemical Biology, 2019)
Infections with Clostridioides difficile (formerly Clostridium difficile) have increased in incidence, morbidity, and mortality over the past decade. Preventing infections is becoming increasingly important, as frontline antibiotics become less effective and frequently induce recurrence by disrupting intestinal microbiota. The clinically most advanced vaccine approaches prevent symptoms once C. difficile infection is established by inducing immunity to secreted clostridial cytotoxins. However, they do not inhibit bacterial colonization and thereby favor asymptomatic carriage. Synthetic oligosaccharides resembling the C. difficile surface glycans PS-I, PS-II, and PS-III are immunogenic and serve as basis for colonization-preventing vaccines. Here, we demonstrate that glycoconjugate vaccine candidates based on synthetic oligosaccharides protected mice from infections with two different C. difficile strains. Four synthetic antigens, ranging in size from disaccharides to hexasaccharides, were conjugated to CRM197, which is a carrier protein used in commercial vaccines. The vaccine candidates induced glycan-specific antibodies in mice and substantially limited C. difficile colonization and colitis after experimental infection. The glycoconjugates ameliorated intestinal pathology more substantially than a toxin-targeting vaccine. Colonization of the gut by C. difficile was selectively inhibited while intestinal microbiota remained preserved. Passive transfer experiments with anti-PS-I serum revealed that protection is mediated by specific antiglycan antibodies; however, cell-mediated immunity likely also contributed to protection in vivo. Thus, glycoconjugate vaccines against C. difficile are a complementary approach to toxin-targeting strategies and are advancing through preclinical work.
CRIS-Team Scopus Importer:2019-12-03

Synthetic oligosaccharide-based vaccines protect mice from Clostridium difficile infections - Mattner, Jochen; Enßer, Armin; Seeberger, P. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

The CD83 molecule expressed by dendritic cells is a checkpoint to regulate resolution of inflammation as well as homeostasis within periphery and CNS - Wild, Andreas; Krzyzak, Lena; Mattner, Jochen; Winkler, Thomas; Nitschke, Lars; Steinkasserer, Alexander (2018)
EVALuna2:36214

The interplay between dendritic cells and CD8 T lymphocytes is a crucial component of SARS-CoV-2 immunity - Buttenschön, Jonas; Mattner, Jochen (Cellular & Molecular Immunology, 2021)
CRIS-Team Scopus Importer:2021-01-15

The Role of Adaptor Proteins in the Biology of Natural Killer T (NKT) Cells - Gerth, Evelyn; Mattner, Jochen (Frontiers in Immunology, 2019)
Adaptor proteins contribute to the selection, differentiation and activation of natural killer T (NKT) cells, an innate(-like) lymphocyte population endowed with powerful immunomodulatory properties. Distinct from conventional T lymphocytes NKT cells preferentially home to the liver, undergo a thymic maturation and differentiation process and recognize glycolipid antigens presented by the MHC class I-like molecule CD1d on antigen presenting cells. NKT cells express a semi-invariant T cell receptor (TCR), which combines the V alpha 14-J alpha 18 chain with a V beta 2, V beta 7, or V beta 8 chain in mice and the V alpha 24 chain with the V beta 11 chain in humans. The avidity of interactions between their TCR, the presented glycolipid antigen and CD1d govern the selection and differentiation of NKT cells. Compared to TCR ligation on conventional T cells engagement of the NKT cell TCR delivers substantially stronger signals, which trigger the unique NKT cell developmental program. Furthermore, NKT cells express a panoply of primarily inhibitory NK cell receptors (NKRs) that control their self-reactivity and avoid autoimmune activation. Adaptor proteins influence NKT cell biology through the integration of TCR, NKR and/or SLAM (signaling lymphocyte-activation molecule) receptor signals or the variation of CD1d-restricted antigen presentation. TCR and NKR ligation engage the SH2 domain-containing leukocyte protein of 76kDa slp-76 whereas the SLAM associated protein SAP serves as adaptor for the SLAM receptor family. Indeed, the selection and differentiation of NKT cells selectively requires co-stimulation via SLAM receptors. Furthermore, SAP deficiency causes X-linked lymphoproliferative disease with multiple immune defects including a lack of circulating NKT cells. While a deletion of slp-76 leads to a complete loss of all peripheral T cell populations, mutations in the SH2 domain of slp-76 selectively affect NKT cell biology. Furthermore, adaptor proteins influence the expression and trafficking of CD1d in antigen presenting cells and subsequently selection and activation of NKT cells. Adaptor protein complex 3 (AP-3), for example, is required for the efficient presentation of glycolipid antigens which require internalization and processing. Thus, our review will focus on the complex contribution of adaptor proteins to the delivery of TCR, NKR and SLAM receptor signals in the unique biology of NKT cells and CD1d-restricted antigen presentation.
CRIS-Team WoS Importer:2019-07-09

The role of lipids in host microbe interactions - Lang, Roland; Mattner, Jochen (Frontiers in Bioscience, 2017)
Lipids are one of the major subcellular constituents and serve as signal molecules, energy sources, metabolic precursors and structural membrane components in various organisms. The function of lipids can be modified by multiple biochemical processes such as (de-)phosphorylation or (de-)glycosylation, and the organization of fatty acids into distinct cellular pools and subcellular compartments plays a pivotal role for the morphology and function of various cell populations. Thus, lipids regulate, for example, phagosome formation and maturation within host cells and thus, are critical for the elimination of microbial pathogens. Vice versa, microbial pathogens can manipulate the lipid composition of phagosomal membranes in host cells, and thus avoid their delivery to phagolysosomes. Lipids of microbial origin belong also to the strongest and most versatile inducers of mammalian immune responses upon engagement of distinct receptors on myeloid and lymphoid cells. Furthermore, microbial lipid toxins can induce membrane injuries and cell death. Thus, we will review here selected examples for mutual host-microbe interactions within the broad and divergent universe of lipids in microbial defense, tissue injury and immune evasion.
EVALuna2:7757